The Availability, Utilization and Efficacy of Community Resources in the Teaching and Learning of Science for Knowledge Transfer in Senior Secondary Schools in Akwa Ibom State, Nigeria - Akpan, Iniobong Fred; Babayemi, John Olakunle (NIU Journal of Social Sciences; Vol 8 No 2 (2022): NIU Journal of Social Sciences, Vol. 8 No. 2, June 2022, 2022)
The study was examined the availability, utilization and efficacy of community resources in the teaching and learning of science for knowledge transfer in senior secondary schools in Akwa Ibom State, Nigeria. The research design was a descriptive survey. The population for the study was all science teachers from both private and public secondary schools in the State. A total of 480 samples were used. A questionnaire titled “Science Teachers Use of Community Resources in Instructional Delivery (STUCRID) questionnaire was used to collect data for the study. Three research questions and a null hypothesis were formulated to guide the study. Findings revealed that: Private and public secondary schools in Akwa Ibom State lacked most community resources for science delivery, some of the community resources available were not utilized, science teachers’ rating of the efficacy of community recourses in instructional delivery was high and there was no significant difference in the use of community resources between private and public secondary school science teachers (t= 0.130, df=478;p>.05). It was concluded that for science teachers to be effective in carrying out their instructional functions, there is need to harness and use the abundant resources of the surrounding communities in their teaching. Keywords : Availability, Utilization, Efficacy of Community Resources, Knowledge Transfer, School Type.